A review of hydrazide-hydrazone metal complexes’ antitumor potential - Ribeiro, Nádia; Correia, Isabel (Frontiers in Chemical Biology, 2024)
Cancer inflicts a tremendous burden on modern society, and more effective and selective treatments need to be developed. Metallodrugs have been extensively explored as alternatives to current chemotherapeutic regimens that suffer from shortcomings such as severe side effects and acquired resistance. Hydrazide-hydrazones are a family of organic molecules containing the hydrazone functionality attached to a carbonyl group (-C=N-NH-CO). These molecules are extremely versatile and can be obtained from modular reactions between hydrazides and aldehydes or ketones, of with which a largehuge library of these beingis available commercially available. Hydrazide-hydrazones show numerous therapeutic effects, and typically, their metal complexes exhibit increased potency. This review aims to highlight the potential of hydrazide-hydrazone metal complexes in the field of anticancer research. It focuses on the literature published in the last 10 years of research (2013-2023) and describes their biological effects, their anticancer antiproliferative activity and their mechanisms of action. It is organized by metal ion, and includesincluding Cu, Ru, Pt, Pd, V, other d-block, lanthanide, and non-d-blockGa and Sn ions. It highlights the variety diversity of molecules being developed and can be used as a guide for developing new hydrazide-hydrazones as efficient anticancer agents.